Óxido de magnésio, gesso e micronutrientes como fertizante granulado em coffea canephora - Altoé, Arieli (2013)
The dolomitic limestone is still the most used source to meet the demand of coffee in magnesium, requiring the development of fertilizers that are economically viable sources of magnesium fertilizers for annual replacement of this element. This study aime